Application of coated hollow fiber protected membrane liquid phase microextraction to the analysis of organophosphorus pesticides - Roharjo, Yanuardi (Penerbit UTM, 2008)
This paper evaluates a m ethod for determ ining the organophosphorus pesticides (m ethidation, quinalphos and profenofos) in aqueous sam ple using coated hollow fiber protected liquid phase m icroextraction syst em (CHF-LPME) coupled with reversed phase high perform ance liquid chrom atography (RP- HPLC) with UV-Vis detection. Po lypropylene fiber coated with polydim ethylsiloxane (PDMS) wa s developed using the sol- gel technology. The physical characteri stics of the coated fiber was exam ined by Fourier transfor m infr ared (FTIR) a nd field em ission- scanning electron m icroscopy (FE -SEM) equipped with energy dispersive x-ray (EDX). In the pr econcentration step, the accepto r phase (4 µL) introduced into the hollow fiber (1.5 c m) was used to extract organophophorus pesticides fr om aqueous sam ple (11 m L). The lim it of detection (LOD) obtained varied from 16.9 to 0.65 µg L -1 . The proposed m ethod provided good enrichm ent factors of up to 219, with reproducibility rang ing from 0.39 to 2.92%, and recoveries of over 75%. This method was applied successfully to the determination of organophosphor us pesticides in selected drinking water samples.